Multilingualism and policy making in Greater China: ideological and implementational spaces - Shen, Qi; Gao, Xuesong (Language policy, 2019)
In this opening commentary, we draw on Ruiz’s (NABE J 8:15–34, 1984 ) metaphorical representations of language to outline the ideological and implementational spaces for language policy making in Greater China. In particular, we highlight how the ‘resource’ orientation allows different stakeholders to negotiate the development of language policies that may help preserve linguistic diversity within a tradition of seeing linguistic unity as foundational to national unity. To illustrate this, we present an analysis of media texts on a major language policy initiative in mainland China and examine relevant discussions in other Chinese contexts. We contend that this ‘resource’ orientation has a significant role in defining the implementational space for language policy making in Greater China, despite the critique that may be levelled at it.